Effect of Hypertension on Outcomes of High-Risk Patients After BCG-Treated Bladder Cancer: A Single-Institution Long Follow-Up Cohort Study. Issue 9 (March 2015) - Dal Moro, Fabrizio; Bovo, Alberto; Crestani, Alessandro; Vettor, Roberto; Gardiman, Marina P.; Zattoni, Filiberto
Abstract : Abstract: Immunotherapy with Bacillus Calmette–Guérin (BCG) is the most efficacious treatment for high-risk bladder cancer (BC) (Ta/T1 or carcinoma in situ) to reduce the risk of recurrence. Our aim was to evaluate whether hypertension and diabetes influence the outcome of patients with noninvasive BC treated with BCG instillations. In order to collect homogeneous data, we considered as "hypertensive" only those patients who had previous diagnosed hypertension and a history of taking medical therapy with antihypertensive drugs (AHT), and as "diabetic" only those prescribed oral antidiabetics or insulin (ADT). We analyzed 343 high-risk BC patients undergoing BCG (1995–2010) with a median follow-up of 116 months (range 48–238). The distribution of various kinds of AHT and antidiabetic drugs was homogeneous, with no significant differences ( p > 0.05). In both univariate and multivariate analyses, the only statistically significant parameter prognostic for recurrence after BCG treatment was AHT. Recurrence-free survival curves showed a significant correlation with AHT ( p = 0.0168, hazards ratio [HR] 1.45, 95% confidence interval [CI] 1.0692–1.9619); there was no correlation ( p = 0.9040) with ADT (HR 0.9750, 95% CI 0.6457–1.4721). After stratification of AHT and ADT according to drug(s) prescribed, there were no significant differences in the BC recurrence rate ( p > 0.05). In this study with a very long-term follow-up, hypertension alone (evaluated by AHT) revealed the increased risk of BC recurrence after BCG treatment. Several hypotheses have been formulated to support these findings, but further prospective studies are needed to both evaluate the real influence of hypertension and identify a possible prognostic factor to be used in selecting poor-prognosis BC patients as early candidates for surgical treatment.